Kinetics of the hydrogen absorption and desorption processes of hydrogen storage alloys: A review - Li, Qian; Lin, Xi; Luo, Qun; Chen, Yu’an; Wang, Jingfeng; Jiang, Bin; Pan, Fusheng (International journal of minerals, metallurgy and materials, 2022)
High hydrogen absorption and desorption rates are two significant index parameters for the applications of hydrogen storage tanks. The analysis of the hydrogen absorption and desorption behavior using the isothermal kinetic models is an efficient way to investigate the kinetic mechanism. Multitudinous kinetic models have been developed to describe the kinetic process. However, these kinetic models were deduced based on some assumptions and only appropriate for specific kinetic measurement methods and rate-controlling steps (RCSs), which sometimes lead to confusion during application. The kinetic analysis procedures using these kinetic models, as well as the key kinetic parameters, are unclear for many researchers who are unfamiliar with this field. These problems will prevent the kinetic models and their analysis methods from revealing the kinetic mechanism of hydrogen storage alloys. Thus, this review mainly focuses on the summarization of kinetic models based on different kinetic measurement methods and RCSs for the chemisorption, surface penetration, diffusion of hydrogen, nucleation and growth, and chemical reaction processes. The analysis procedures of kinetic experimental data are expounded, as well as the effects of temperature, hydrogen pressure, and particle radius. The applications of the kinetic models for different hydrogen storage alloys are also introduced.